2013
DOI: 10.21608/ejabf.2013.2184
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of European hake Merlucciusmerluccius (Linnaeus, 1758) in the Egyptian Mediterranean waters

Abstract: The reproductive biology of the European hake (Merlucciusmerluccius, Linnaeus, 1758) was studied in the Egyptian Mediterranean waters from December 2009 to November 2011. The sex ratio revealed that males dominated the catch in groups from 13.0 to 32.0 cm, while females dominated for larger groups (33.0-47.0 cm). Generally, males dominated the catch in all seasons. Length at first sexual maturity was found to be 21.8 cm and 24.0 cm for males and females respectively. For both sexes gonadosomatic index reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In this study, the monthly trend of GSI seems to define a sole reproductive event during the year that extended from November to March with a peak in February. The spawning season here estimated for the Egyptian Mediterranean Sea, including the period between November and March, is also reported by (Al-Absawy, 2008;Philips and Ragheb, 2013) in Egyptian Mediterranean water, as well as in the central and western Mediterranean Sea (Carbonara et al, 2019), the eastern central Atlantic Moroccan coast (Habouz et al, 2011) and in the Sea of Marmara, Turkey (Kahraman et al, 2017). Other authors identified a different period of the spawning season.…”
Section: Total Lengthsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, the monthly trend of GSI seems to define a sole reproductive event during the year that extended from November to March with a peak in February. The spawning season here estimated for the Egyptian Mediterranean Sea, including the period between November and March, is also reported by (Al-Absawy, 2008;Philips and Ragheb, 2013) in Egyptian Mediterranean water, as well as in the central and western Mediterranean Sea (Carbonara et al, 2019), the eastern central Atlantic Moroccan coast (Habouz et al, 2011) and in the Sea of Marmara, Turkey (Kahraman et al, 2017). Other authors identified a different period of the spawning season.…”
Section: Total Lengthsupporting
confidence: 79%
“…It was found that lengths over 53 cm TL were 100% female. In the same geographical area, Philips and Ragheb (2013) observed a different result, as did Pieiro and Sanza (2003) in Iberian Atlantic waters where mails dominate the catch. This difference could be due to several factors related to different growth rates; time and method of sampling; adaptation to the reproductive behaviour of the population; environmental conditions and food availability (Nikolsky, 1963;Vandeputte, 2012).…”
Section: Discussionmentioning
confidence: 75%
“…Thus, seasonal changes in the availability of prey can significantly impact the diet of M. merluccius . The increase of ingested pelagic Osteichthyes in the autumn season could be explained by fish movements to shallow parts for reproduction, since the spawning season estimated for M. merluccius in the eastern, central, and western Mediterranean Sea [ 28 , 79 ] and the eastern central Atlantic Moroccan coast [ 48 ] occurred in the autumn season from November to March.…”
Section: Discussionmentioning
confidence: 99%